2021
DOI: 10.1186/s41239-021-00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cyberloafing in computer laboratory teaching settings

Abstract: This correlational study investigated the factors affecting cyberloafing behavior in an educational environment, specifically that of a computer laboratory teaching setting. A total of 272 students selected using convenience sampling responded to a questionnaire that collected data about cyberloafing behavior and student demographics, personality type, sense of belonging, motivation, locus of control and teacher evaluation (respect, activities, communication, motivation) as well as computer lab teaching settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 95 publications
0
9
0
1
Order By: Relevance
“…On the other hand, some of the scholars addressed prevalence rates of cyberloafing activities. They demonstrated that high school students cyberloaf mostly for socialization purposes, followed by purposes of news follow up and personal business (Baturay & Toker, 2015 ; Toker & Baturay, 2021 ). Likewise, university students mostly report socialization purposes as the underlying reason for using the Internet, followed by playing games and surfing (Hacıoğlu Deniz & Karakaş Geyik, 2015 ).…”
Section: Cyberloafing Behaviors In Educational Settingsmentioning
confidence: 99%
“…On the other hand, some of the scholars addressed prevalence rates of cyberloafing activities. They demonstrated that high school students cyberloaf mostly for socialization purposes, followed by purposes of news follow up and personal business (Baturay & Toker, 2015 ; Toker & Baturay, 2021 ). Likewise, university students mostly report socialization purposes as the underlying reason for using the Internet, followed by playing games and surfing (Hacıoğlu Deniz & Karakaş Geyik, 2015 ).…”
Section: Cyberloafing Behaviors In Educational Settingsmentioning
confidence: 99%
“…Although the students' motivation to learn is affected by many factors, the most critical factor is the teacher. Studies have shown that teachers who are unprepared for the lesson, speak with an unwilling tone, do not take care of students, do not activated them in the lesson, and make negative judgments about students' performances, negatively affect student motivation (Lamb, 2017;Toker & Baturay, 2021). This situation makes us think that faculty of education instructors also just focus on transferring information during the lessons, that they do not use techniques to activate students in the lesson or that they cannot communicate well with them.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Bununla birlikte yapılan araştırmalar öğrencilerin motivasyonlarının ortaya çıkmasında veya azalmasında en kritik faktörün öğretmen davranışları olduğunu göstermektedir. Elde sonuçlara göre öğretmenlerin verimli ders işlememe, hazırlıksız derse girme (Ünal, 2013), isteksiz ve coşkudan uzak bir ses tonuyla konuşma (Yıldırım, Ünal ve Sürücü, 2015), öğrencilerle ilgilenmeme (Sürücü ve Ünal, 2018), öğrencilerin amaçlarını ve yöntem tercihlerini ihmal etme (Lamb, 2017), olumsuz yargılarda bulunma (Ünal ve Gürsel, 2015), öğrencilere saygı duymama (Toker ve Baturay, 2021) davranışları öğrencilerin motivasyonlarını olumsuz etkilemektedir. Dolayısıyla bu sonuçlar öğretim elemanlarının derslerde ağırlıklı olarak bilgi aktarmaya odaklandığını, öğrencileri derste aktif kılacak süreçler izlemediklerini veya onlarla sağlıklı bir şekilde iletişime geçemediklerini düşündürmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…It is seen that the studies in the literature have been generally conducted with university students, teachers and in areas using ICT tools (e.g. Akbulut, Dursun, Dönmez and Şahin, 2016;Rana, Slade, Kitching, and Dwivedi, 2019;Toker and Baturay, 2021;Yılmaz and Yurdagül, 2018). It is observed that the studies carried out, especially with middle school students are in the minority in the international framework.…”
Section: Introductionmentioning
confidence: 99%